Mixing and crystallization : selected papers from the International Conference on Mixing and Crystallization held at Tioman Island, Malaysia in April 1998 - Gupta, B.S. (Kluwer Academic, 2000)
Foreword. Mixing. CFD Modelling of Hydrodynamic Conditions within the Wake of Mixing Impeller Blades; G.D. Rigby, et al. Visualisation and quantification of laminar flow mixing in a stirred tank reactor; M. Liu, et al. Turbulence structure and isotropy in stirred vessels; K.C. Lee, et al. A study of agitated gas-liquid reactors with concave blade impellers; Z.D. Chen, J.J.J. Chen. Studies of aerated mixing with multiple axial flow hydrofoil (APV-B2) impellers; W. Bujalski, et al. Interstage backmixing of a gas-liquid multistage, mechanically-agitated, compartmented column; M.S. Takriff, et al. Mass transfer in a plunging liquid jet; G.M. Evans, et al. An optimum concentration for the suspension of solids in stirred vessels; G.R. Drewer, et al. Crystallization. Freeze concentration with ice-lining in a crystallizer of agitated vessel; Y. Yamazaki, et al. How agglomeration Processes affect experimentally determined nucleation rates; H. Schubert, A. Mersmann. On-line measurement of solids distribution I stirred tanks and crystallizers using electrical computed tomography; R.A. Williams, et al. A new expression for dispersedness of multi-phase taking account of consideration of local size distribution; K. Ogawa, et al. Size dependent classification function in imperfectly mixed suspension continuous crystallizer; Z. Sha, S. Palosaari. An experimental study to the effects of supersaturation ratio, impeller design and Impeller speed on agglomeration of aluminium trihydroxide; M.L.J. van Leeuwen, et al. The precipitation of silica from acidic zinc leach liquors; R.M. Cooper, et al. Precipitation of microcrystals of salicylic acid na T mixer: experimental study and Modelling; V. Nallet, et al. Mixing, reaction and precipitation: The Barium Sulphate Precipitation System; N.S. Tavare. Micromixing in a Single Feed Semibatch Precipitation Process; R. Philips, et al. Yield Model of a Batch Gibbsite Precipitator; A. Futia, et al. Modelling a Constant Supersaturation Precipitator; T.S. Li, et al. How to Influence the Median Crystal Size of Precipitates; A. Mersmann, et al. Modeling Fluctuations in the Growth Rate of a Single Crystal; L.T. Fan, et al. Modeling the Attrition Process in a 22 Liter Draft Tube Crystallizer; A.M. Neumann, et al. Computational Fluid Dynamics Approach to Precipitation Reactions: The Importance Of Subgrid-Scale Fluctations; M.L.J. van Leeuwen, et al. Scaling-up of Reactive Crystallizers; J.G. Wijers, et al. In-situ Measurement Method of Crystal Concentration in a Seeded Batch Crystallizer; T. Nomura, et al. Monte Carlo Simulation of the Crystal Size Distribution with Attrition Effects in a Mixed Suspension Crystallizer; K.C. Lim, et al. A Review of the Crystallization of Sugar; E.T. White.